Analysis of the Role of Legal Politics and Challenges in Post-Reformation Legal Reform - Ismaidar Ismaidar; Tamaulina Br Sembiring; Muhammad Faiz Hadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Legal politics is one of the central concepts in the legal system which is closely related to state policy in the formation, application and change of law. This article examines the role of legal politics in legal reform in Indonesia post-1998 reform, with a focus on the challenges faced in implementing legal policies as well as evaluating the effectiveness of the changes that have been made. This research uses a qualitative approach with analytical descriptive methods, which aims to describe how legal politics can be an instrument that determines the direction and substance of legal reform in Indonesia. The results of this research show that although there has been progress in legal reform, major challenges still exist, especially related to the implementation of legal policies which are influenced by political dynamics which do not always support the creation of an effective and just legal system.